Pendayagunaan Irigasi Airtanah Menunjang Budidaya Tanaman Secara Produktif pada Lahan Kering - Muhammad Aqil; R.H. Anasiru; I.U. Firmansyah; Riyadi Riyadi; Sigit S. Arief (agriTECH, 2002)
The utilization of shallow groundwater well to support cropping pattern in dry land area should be directed to increase land and water productivities through proper irrigation management and effective operation of groundwater irrigation pump. By the concept that a certain plant needs a certain amount of transpired water through it's leaves to produce 1 kg dry product during it's production cycle, an attempt is done to determine technical and economic aspects of the groundwater irrigation system to utilize water and energy efficiently by improving the conjunctive use of rainfall and groundwater irrigation in dry land area. A set of centrifugal pump (ɸ 2") was used to lift water from the shallow groundwater well at total head of 22 m (Suction head = 12 m and delivery head = 10 m) and was used to irrigate maize, peanut and onion crops. The result obtained indicateds that the introduced technology is suitable to be applied at farm level. In order to reduce operational cost of pump, simulation was done to determine the most appropriate planting achedule using computer simulation model. By taking planting schedule back approximately 2 weeks reducing annual irrigation requirement of 500 to 600 m3/ha and reduce annual operation pump of 66.5 hour/ha/year. Advanced analysis using economic feasibility analysis indicates technology introduced suitable to applied with B/C ratio = 1.25 (maize), 1,83 (peanut) and 2,36 (onion).